KETAHANAN HIDUP BEBERAPA JENIS TUMBUHAN DI KAWASAN VOID BEKAS TAMBANG BATUBARA - Kissinger Kissinger; Rina Muhayah Noor Pitri (Universitas Lambung Mangkurat, 2018)
The selection of plant species for phytoremediation activities is very important in the conservation of soil, water, plant, and animal life to create a conducive environment within a community or ecosystem. Plant survival is one indication for the selection of phytoremediation plants. This study aims to determine the survival of some plants in void areas of coal mining. Types of plants used are surface water plants species and the edge of void plant species. The plants of surface water area consisting of Kiambang (Salvinia sp.), Enceng gondok (Eichornia crassipes), Genjer (Limnocharis flava), and Kangkung (Ipomoea aquatica). The plants which planted on edge of void were purun tikus (Eleocharis dulcis) and Bamban (Donax canniformis). Time of observation time was 6 months. Data were analyzed using a tabular matrix that contained the percentage of plant life/period time. The growth of the plant is specifically defined according to the color visibility and the development of plant form. The results of the study found that the highest surface survival species were Kiambang (Salvinia sp.) and Kangkung (Ipomoea aquatica). Both of them still survive for 6 months of observation. The growth percentage of these two plants at the end of the observations are 36% and 20% respectively. Enceng gondok (Eichhornia crassipes) has a survival for 4 months. Whole water plant growth was depressed by indications of death, tendencies to yellowish-brownish or blackish, and smaller body parts. Purun tikus (Eleocharis dulcis) and Bamban (Donax canniformis) grown on the edge of voids have a high survival. Both of them showed ≥95% survival at the end of observation time.